If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14y + 15 = 48y Reorder the terms: 15 + 14y = 48y Solving 15 + 14y = 48y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-48y' to each side of the equation. 15 + 14y + -48y = 48y + -48y Combine like terms: 14y + -48y = -34y 15 + -34y = 48y + -48y Combine like terms: 48y + -48y = 0 15 + -34y = 0 Add '-15' to each side of the equation. 15 + -15 + -34y = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -34y = 0 + -15 -34y = 0 + -15 Combine like terms: 0 + -15 = -15 -34y = -15 Divide each side by '-34'. y = 0.4411764706 Simplifying y = 0.4411764706
| 5(3x-2)=-10 | | 14y+15=48 | | 2x+2(5x-8)=44 | | (2x-3)(x^2-9)=0 | | -4x-9=27 | | 45.9+K=1.1 | | 4x+8y=56 | | (x-3)(4x-3)=0 | | 2d+1/6=(1/3d+1) | | 8z-24=16 | | 3=-17+t/5 | | 17c-3c=4c | | 4a=45+2a | | -12=8z | | (x^5)+8*(ln(y))=7 | | 2(2x-1)=3(x-1) | | 3(5x+7)=-46+52 | | -12(x+6)-6(x-6)=-x+x | | 6z-9-2z+5=0 | | 55.6=k-0.9 | | 4(x+9)=6x+2-2x+34 | | 21z^2-2z-3=0 | | 3m+6(1+6M)=84 | | x/2-3=-6 | | (2y+4y)+-1(y+9)=26 | | a^2-4a+5= | | (x^5)+8lny=7 | | 96x-16x^2=0 | | (2y+4y)+-1(y+9)=2 | | 12r+4=79 | | fying(2y+4y)+-1(y+9)=26 | | h^2+3hj-88j^2= |